Condition and Defect Surveys on Penang Heritage Centre: A Case Study on Georgetown World Heritage Building - Othman, Masyatul Husna; Othuman Mydin, Md Azree (Eftimie Murgu University of Resita, 2012)
Condition and defect surveys are process which appropriate experts investigates the existing condition of a building, carry out necessary tasks, evaluate the data collected, make the recommendations professionally about the remedial and predict performance of the building. This paper focuses on condition and defect surveys on Penang Heritage Centre, Malaysia. This building is listed as one of the buildings under Georgetown World Heritage Site. Penang Heritage Trust is a heritage shop house designed with Southern Chinese Eclectic Style. It has Chinese, European and Indian style influence. Chinese style influence on the carved timber door, air vents, gable and end, air-well and etc. While, European and Indian influences can be seen from the design of the louvered shutters and U/V-shaped terracotta roof tiles.